Oh Knit / Muhd 'Afif Hakimi Mohd Narin - Mohd Narin, Muhd 'Afif Hakimi (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Oh Knit is a crochet plushie. The name 'Oh Knit' reflects the material and techniques used in producing this toy! The product tagline is " ... is all i need" which means the plushie toy could a companian and that is all they need. USP of the product is it is custom made requested by the customer. Oh Knit is a product originally belonged to Nurhana binti Mohd Al Mansor and Knitsunny.my. This product is targeted mainly for children.The concept of Oh Knit is childish, colourful, cheerful, child-friendly and joy since the main product is created for children. Hence, the colour schemes are bright and full of joy.There are similar products in the market such as Chubby Plushies, crochet.toy.x, kait.bymas, Crochet My Hobby Crochet Toys Pattern etc. Oh Knit has changed the strategy in promotional marketing, which is targeting social media such as TikTok, Twitter, Facebook and lnstagram because it wants to expand product marketing. In conclusion, Oh Knit has proposed a new concept and a new art direction which helps to bring a new image to help promote local products which has a lot of potential to be in the local and international market. Oh Knit, ... is all i need!